2020
DOI: 10.3389/fonc.2020.579625
|View full text |Cite
|
Sign up to set email alerts
|

Tre2-Bub2-Cdc16 Family Proteins Based Nomogram Serve as a Promising Prognosis Predicting Model for Melanoma

Abstract: Tre2-Bub2-Cdc16 (TBC) proteins are conserved in eukaryotic organisms and function as negative feedback dominating the GAPs for Rab GTPases, while the function of TBC proteins in melanoma remains unclear. In this study, we observed the differential expression of 33 TBC genes in TCGA datasets classified by clinical features. Seven prognostic-associated TBC genes were identified by LASSO Cox regression analysis. Mutation analysis revealed distinctive frequency alteration in the seven prognosticassociated TBCs bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Several studies have stated that a dysregulated TBC family expression is involved in various human diseases such as cancer, obesity and X-linked early-onset nephrotic syndrome and so on 46 49 . There are few reports on TBC1 domain family members in tumor, but the available studies suggest that it mostly functions as an oncogene in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have stated that a dysregulated TBC family expression is involved in various human diseases such as cancer, obesity and X-linked early-onset nephrotic syndrome and so on 46 49 . There are few reports on TBC1 domain family members in tumor, but the available studies suggest that it mostly functions as an oncogene in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…CDC16 has a connection with multiple neurodevelopmental disorders ( 50 , 51 ). It has been found that CDC16 has potential therapeutic function in melanoma ( 52 ). ITPK1 may serve as biomarkers for GC pathogenesis ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…GSEA and clusterProfiler are used to analyze the Reactome path and define each functional cluster, and false detection rate (FDR) < 0.25, P < 0.05 was considered significant enrichment. The GSVA was used to execute the functional enrichment analysis to clarify the unique signaling pathways of variation trend of differentially expressed genes in fast responder and slow responder with psoriasis, and define the |correlation coefficient | > 0.5 cut-off value ( 16 ).…”
Section: Methodsmentioning
confidence: 99%